ASSOCIATION OF DIFFERENT RISK FACTORS IN PREVALENCE OF CEREBRAL INFARACTION - Malik, Saqib; Pervez, Alia; Zainab, Zarnab (Journal of Ayub Medical College Abbottabad, 2018)
Background: Cerebral infraction is one of the important causes of cerebrovascular accident. This study was conducted to see which risk factors are more prevalent in cerebral infraction. Methods: It is a hospital based descriptive study of 130 patients of different types of strokes. Results: Out of 130 patients 70 were male and 60 females. Majority (58%) of the patients were between 41-60 years of age. Patient presented with variable risk factors. The majority (60% male and 73% female) were hypertensive. The percentage of other factors including diabetes mellitus, atrial fibrillation, smoking, high serum cholesterol, obesity and carotid artery stenosis was observed. Conclusions: Cerebral infraction is the most common cause of stroke in our community and all the other factors that are included in our study showed their association in occurrence of cerebral infraction. Keywords: cerebral infarction; diabetes mellitus; hypertension; smoking